La impugnación administrativa en la nueva ley migratoria chilena - Harris Moya, Pedro (2022)
The entry into force of the Law No. 21325 in Chile in 2021 has not only reformed judicial review in matters of migration and foreigners, it has also introduced significant modifications to administrative appeal, under the application of basic administrative laws. Apparently, this law has increased the effectiveness of such claims if they are exercised against nonexpulsive acts (having established their compatibility with other appeals and, likewise, the suspension of the effects of the contested acts) and excluded the application of administrative appeals against an expulsion measure. However, this first interpretation can admit other interpretations. The administrative appeal against non-expulsive acts may impose restrictions on the rights of the claimant, in line with certain interpretative criteria developed by the case law in Chile. Likewise, the ineffectiveness of such claims against expulsive acts may be corrected, in accordance with the constitutional guarantees regarding the exercise of these mechanisms.